CTA Project Completion Report: ICT Update - Addison, Chris; Muyiramye, Didier; Staden, Paul van (Technical Centre for Agricultural and Rural Cooperation, 2020)
The ICT Update magazine has been running for over 20 years, originating as an e-mail newsletter, and developing into a print magazine and website. Since 2018 a number of changes were implemented, and 12 issues have been produced in English and in French. A number of activities were undertaken to make the magazine more cost effective and more inclusive.